2023
DOI: 10.19127/bshealthscience.1167822
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parents' Health Literacy Level on the Attitudes and Behaviors of Childhood Vaccinations

Abstract: Objective: Health literacy is important for parents to correctly perceive and implement decisions about their children's health. Health literacy of parents can affect their understanding of the requirements of preventive treatments and their positive attitudes and behaviors towards childhood vaccines. The global growth of vaccine hesitations in recent years has led to increasing concern at WHO. Therefore, the level of health literacy may be important in experiencing vaccine hesitancy. For this reason, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…We observed that parents who were exposed to negative news and could not find the correct information or could not adequately distinguish between reliable and unreliable knowledge had more negative attitudes toward the COVID-19 vaccination. Our study results were in agreement with the results that parents who accessed the correct information and benefited from scientific pages on the Internet had more positive attitudes toward the COVID-19 vaccination in the literature ( Dağlı & Topkara, 2023 ; Engelbrecht et al, 2022 ; Kocamaz & Kocamaz, 2022 ; Siewchaisakul et al, 2022 ; Ünlü & Yıldıray, 2021 ; Yigit et al, 2021 ; Yıldız et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that parents who were exposed to negative news and could not find the correct information or could not adequately distinguish between reliable and unreliable knowledge had more negative attitudes toward the COVID-19 vaccination. Our study results were in agreement with the results that parents who accessed the correct information and benefited from scientific pages on the Internet had more positive attitudes toward the COVID-19 vaccination in the literature ( Dağlı & Topkara, 2023 ; Engelbrecht et al, 2022 ; Kocamaz & Kocamaz, 2022 ; Siewchaisakul et al, 2022 ; Ünlü & Yıldıray, 2021 ; Yigit et al, 2021 ; Yıldız et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…With the opening of schools, the fact children were actively infected with COVID-19 and survived with mild symptoms may have reduced the perception of the need for vaccination. In addition, the low number of deaths from COVID-19 in children and the fact that COVID-19 often shows mild symptoms created the perception that it is not necessary to vaccinate children against COVID-19 ( Dağlı & Topkara, 2023 ; Kocamaz & Kocamaz, 2022 ; Ünlü & Yıldıray, 2021 ; Yigit et al, 2021 ; Yıldız et al, 2021 ). These factors may have led to a negative attitude toward the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation